Digital revascularization and replantation using the wide-awake hand surgery technique. (July 2017) - Wong, JKF; Lin, CH; Chang, NJ; Chen, HC; Lin, YT; Hsu, CC
The use of local anaesthesia and adrenaline for hand surgery is gaining popularity; however, where vascularity is impaired, wide-awake surgery is considered a contraindication. We present our case series of five digital devascularizations and eight amputations that underwent surgery using the 'wide-awake' anaesthetic technique. A temporary digital tourniquet (< 20 min) was used in three cases to identify structures quickly. The anastomoses were performed under local anaesthesia without a tourniquet. All cases had successful re-establishment of blood flow with good perfusion to the digital tips; no cases were re-explored because of vascular crisis. Four cases had minor superficial soft tissue necrosis that healed secondarily. We conclude that digital revascularization and replantation can be performed under local anaesthesia with use of adrenaline and without detriment to the traumatized digit provided careful patient selection and adequate operator experience are available. Level of evidence: IV